Creasy-Resnik's study guide for maternal fetal medicine. (2023) - Lockwood, Charles J; Moore, Thomas; Copel, Joshua; Silver, Robert M; Resnik, Robert; Louis, Judette; Dugoff, Lorraine
No abstract available